Pengaruh Gaya Kepemimpinan Terhadap Motivasi - Aulia Reski Novianti Alnisyar; Muh Ardiansyah; Andi Wahed (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
This study examines the influence of leadership style on motivation. The research method used in this study is quantitative located at SMA Se, Tamalate District, Makassar City. This type of research is ex-post facto with a total sample of 56 teachers determined by the Random Sampling technique. The instrument used was in the form of a questionnaire with teacher respondents. Data collection tools using questionnaires, data analysis techniques using Descriptive analysis and Inferential analysis. The results showed that (1) The description of the leadership style at the Tamalate High School in Makassar City was more influential on the leadership style of the democratic school principal; (2) The description of motivation in high schools in Tamalate Subdistrict, Makassar City, has more influence on the work motivation of external teachers; (3) There is a significant positive influence between leadership style and motivation in high schools in Tamalate District, Makassar City. The results of the study on simple regression analysis describe the two variables into the regression equation Y = 39.168 + 0.340X. For the t test, a calculation of 2.656 > ttabel 2.004 and the probility (sig) was obtained, it turned out to be 0.010 < 0.05 which means ho is rejected and ha is accepted in other words the leadership style has a significant effect on motivation and for the coefficient of determination known from the R Square value of ,116 this means the simultaneous influence of variable X on variable Y by 11.6% while the remaining 88.4% is influenced by other variables that are not included in this research model.